Antioxidant Compound Quercetin-3-O-α-L-rhamnoside(1→6)- β-D-glucose (Rutin) isolated from ethyl acetate leaf extracts of Memecylon edule Roxb (Melastamataceae) - Srinivasan, Ramalingam; Natarajan, Devarajan; Shivakumar, Muthugounder Subramaniam (Free Radicals and Antioxidants)
Introduction: The present study was aimed to isolate antioxidant principle from leaf ethyl acetate extract of Memecylon edule for the first time. M. edule belongs to melastomataceae family; possess various biological properties and folklore uses. Methods: Isolation of antioxidant compound was carried out by DPPH radicals scavenging activity guided method and employing chromatography techniques (TLC and column chromatography). The structure of isolated bioactive compound (Rutin) was confirmed by using various spectral data like UV, FT-IR, LC-MS, CHNS analysis, 1 H-NMR, 13C-NMR, DEPT-135, HMBC and HSQC. In vitro antioxidant activity of isolated compound was evaluated by using DPPH radical, nitric oxide radical, superoxide radical, hydroxyl radical scavenging assays and ferric reducing antioxidant power assay (FRAP) with reference to ascorbic acid and butylated hydroxyanisole (BHA). One way analysis of variance (ANOVA) and Tukey’s multiple comparison tests were performed. Results: DPPH activity guided isolation resulted isolation of Rutin. Isolated rutin exhibited remarkable scavenging capacity on all tested radicals in a concentration dependent manner. The results also showed that Rutin harbor strong reductive capacity on hydroxyl radicals with lowest IC50 value (17.06 µg/ml) and strong ferric ion (Fe3+) chelation (EC50 value 17.29 µg/ml) potential. Conclusion: The results of the present investigation concluded that the leaf ethyl acetate extract of M. edule is a good source of Rutin which harbor significant antioxidant potential.
Keywords: Antioxidant activity; HMBC; HSQC; Memecylon edule; Rutin